Pengaruh Model Pembelajaran Kooperatif Tipe Make A Match Terhadap Aktivitas dan Hasil Belajar Siswa Pada Materi Sistem Pernapasan Manusia Di Kelas VIII SMP N 5 Sipoholon T.P 2022/2023 - Widya Arwita; Christine Sinaga; Sartika Romauli Sinaga (BEST Journal (Biology Education, Sains and Technology), 2023)
This study aims to determine whether or not there is an influence of the make a match type cooperative learning model on student learning outcomes and activities on human respiratory system material in grade VIII SMP Negeri 5 Sipoholon The method used in the study was quasi-experimental. This study used 2 sample classes with a total sample of 44 students. The experimental class is taught with the Make a Match model and the control class is taught the conventional model. The data collection technique uses learning outcomes tests with multiple-choice questions and student activity observation sheets. The results of the research findings showed that the average score of student learning outcomes in the experimental class (Make A Match) 88 with a standard deviation of 6.75 was higher than the average score of the conventional class which was 62 with a standard deviation of 7.68. Based on the results of the hypothesis test analyzed using SPSS Version 23 shows that there is an influence of the Make a match cooperative type learning model on learning outcomes, this is seen from the value of sig.0.000 ˂ 0.05 with a α of 0.05.While from the calculation of the average results of student activity in the experimental class is 81 with a standard deviation of 6.94 higher than the average value of the control class which is 61 with a standard deviation of 10.59.Based on the results of the hypothesis test shows that there is an influence of the Make a match cooperative type learning model on Student Learning Activities, this can be seen from the sig value of 0.000 ˂ 0.05 with α = 0.05.Keywords :Make A Match, Student Activities,Learning Outcomes, Human Respiratory System,